Agriculturally induced environmental problems in Russia - Igor Shvytov (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 1998)
This paper is concerned with environmental impacts in Russia, focusing in particular on agriculturally induced environmental impacts. First it discusses the current environmental situation in Russia. The paper provides an overview of Russia, including a description of its geographical and bioclimatic resources. The environmental pressures induced by human activity have been covered in more detail. The current situation regarding atmospheric emissions and waste water discharges are also considered in this paper. The environmental impacts of agriculture are stressed, with a focus on land degradation and especially soil erosion. A discussion of some policy suggestions to avoid environmental problems concludes the paper. – – Das vorliegende Diskussionspapier befaßt sich mit Umwelteinwirkungen in Rußland, insbesondere mit solchen, die von der Landwirtschaft ausgehen. Zuerst wird der gegenwärtige Zustand der Umwelt in Rußland beschrieben. Das Diskussionspapier gibt einen knappen Überblick über Rußland, einschließlich einer Beschreibung seiner geographischen und bioklimatischen Ressourcen. Die durch menschliche Aktivitäten verursachten Umwelteinwirkungen werden detaillierter behandelt. Berücksichtigt werden dabei auch die atmosphärischen Emissionen und die Abwasserbeseitigung. Die Untersuchung der Umwelteinwirkungen der Landwirtschaft konzentriert sich auf die Bodendegradation und vor allem auf Erosionsprobleme. Abschließend werden Politikmaßnahmen zur Vermeidung von Umweltproblemen diskutiert.
urn:nbn:de:gbv:3:2-22823
Keywords: 330